FIELD EXPERIENCE AT RILEY COUNTY K-STATE RESEARCH AND EXTENSION - Knutson, Cassandra (My University, 2016)
My field experience at Riley County K-State Research and Extension began in late February of 2016 and lasted until the end of June, 2016. During this time, I completed two hundred and forty hours of experience under the direction and supervision of Virginia (Ginny) Barnard. Ginny is a former Kansas State Master of Public Health (MPH) alum, and is currently employed as the Family and Consumer Sciences agent for the Extension Office in Riley County. As a Family and Consumer Sciences agent, she is primarily responsible for issues relevant to health, nutrition, food safety, and indoor environments. In addition to her many responsibilities, Ginny is a member of numerous coalitions and committees, as well as a collaborator with many community organizations and programs. During my time at Riley County K-State Research and Extension, Ginny allowed me to work with some of these committees, programs, and projects. I was assigned one major project to work on while at the Research and Extension office; work with Riley County Extension, the City of Manhattan’s Bike/PED Coordinator, and the Bicycle/Pedestrian Advisory Committee (BPAC) to develop, organize, and implement a community-wide educational and promotional program designed to increase community awareness and promote cycling for health, active transportation, and as a family-friendly activity.
Keywords: Manhattan, KS Bike Month; Cycling Promotion; Health Promotion; Riley County Extension